2019
DOI: 10.1532/hsf.2493
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Controlling Nutritional Status Score (CONUT) and Prognostic Nutritional Index (PIN) on Patients Undergoing Coronary Artery Bypass Graft Surgery

Abstract: Background: The aim of this study is to evaluate the negative effect of malnutrition in patients with coronary artery disease who are undergoing coronary artery bypass graft surgery. Methods: In this study, we analyzed 149 patients, who underwent coronary artery bypass surgery. Nutritional status of the patients was classified using controlling nutritional status score (CONUT) and prognostic nutritional index (PNI). Statistical correlation between malnutrition and complication following operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…There are not many studies in the literature examining the relationship between carotid artery stenosis and PNI. However, it can be mentioned that there are studies demonstrating that low PNI levels are an indicator of poor prognosis (4,12,13,14,15). Although, we found that lower PNI values was not an independent predictor for CAS progression, low PNI values were statistically significantly in the surgical group.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…There are not many studies in the literature examining the relationship between carotid artery stenosis and PNI. However, it can be mentioned that there are studies demonstrating that low PNI levels are an indicator of poor prognosis (4,12,13,14,15). Although, we found that lower PNI values was not an independent predictor for CAS progression, low PNI values were statistically significantly in the surgical group.…”
Section: Discussioncontrasting
confidence: 79%
“…Similarly, in their study Açıkel et al indicates that PNI is a remarkable prognostic factor for CAD patients undergoing CABG surgery. They state that there is obvious correlation between PNI with morbidity and mortality after CABG surgery (14). Wada et al Investigated the relationship between long-term outcomes after percutaneous coronary intervention and PNI in stable coronary artery disease and found that low PNI values were associated with the increase in the incidence of major adverse cardiac events (4).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the controlling nutritional status (CONUT) score [2], geriatric nutritional risk index (GNRI) [3], and prognostic nutritional index (PNI) are the most useful markers which provide simple, effective, and objective assessments of nutritional status [4]. According to recent studies, these parameters have been shown to be associated with predictors of mortality and morbidity in patients with prior history of heart failure [5][6][7]. Studies also confirmed that these parameters were also associated with clinical outcomes in patients with CAD [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive nutritional indexes, such as the Controlling Nutritional Status (CONUT) score and the Prognostic Nutritional Index (PNI), have been developed and are widely used to evaluate nutritional status [ 14 15 ]. The CONUT score is an easily measured tool for the early detection and ongoing monitoring of nutritional status that is based on serum albumin concentration (an indicator of protein reserves), total cholesterol level (a caloric depletion parameter), and lymphocyte count (an indicator of immune defense) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%